Genetic diversity of fluorescent protein genes generated by gene duplication and alternative splicing in reef-building corals - Takahashi-Kariyazono, Shiho (Zoological Lett, 2015)
INTRODUCTION: Reef-building corals (Scleractinia) exhibit various colors, of which fluorescent proteins (FPs) are a major determinant. Gene duplication is considered a major mechanism in the generation of the FP gene family and color diversity. Examining gene duplication events and subsequent evolution may improve our understanding of FP gene family diversity. RESULTS: We isolated a novel FP gene family from one individual of Montipora sp., which we named monGFP (GFP gene from Montipora sp.). This gene family consists of at least four genes that produce at least six different cDNA sequences. The sequences were categorized into two types based on the length of cDNA; this difference is attributed to alternative splicing. Although the amino acid sequences were different, the emission spectra of the monGFP variants were nearly identical (518–521 nm). In addition to this gene family, we isolated ten paralogous AdiFP10 (Adi-Fluorescent protein-10 gene from Acropora digitifera) sequences from cDNA of two Acropora species, A. digitifera and A. tenuis. Based on our phylogenetic analysis, five sequences from A. digitifera and four sequences from A. tenuis appeared to be in a different cluster from AdiFP10, suggesting a new FP gene cluster. The FP sequences were likely to have been generated independently in each species or generated by gene duplications in the ancestral lineage of Acropora, followed by extensive gene conversion within each species. CONCLUSION: Our results clarify a part of the diversification process of FP genes during the evolutionary history of Montipora and Acropora species. Our analyses of monGFP indicate that FPs translated from different splicing variants and gene copies have evolved without changes in the function of fluorescence, and gene copies have been evolved under purifying selection. On the other hand, AdiFP10 paralogs and other RFP genes in Acropora species may have diversified their functions. Identification of conserved and divergent modes of evolution after the duplication of FP genes may reflect variation in the biological roles of different FPs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40851-015-0020-5) contains supplementary material, which is available to authorized users.